Efek Buah Naga Merah (Hylocereus Polyrhizus) Terhadap Penurunan Kadar Glukosa Darah Pada Diabetes Tipe 2 - Ni Made Indah Ayuni (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Type 2 diabetes mellitus is the most common diabetes in the community, usually occurs at the age of 30 years and over. In type 2 diabetes the pancreas is still able to produce insulin but the insulin produced is poor and cannot function properly to enter glucose into cells, so that it can cause glucose in the blood to increase. Traditional medicine is widely used with the aim of treating and preventing disease, one of which is the red dragon fruit (Hylocereus Polyrhizus). Dragon fruit is rich in antioxidants and contains many substances such as calcium, beta-carotene, vitamin B1, vitamin B2, vitamin C, phosphorus and flavonoids so that it can be used as a therapy to reduce blood glucose levels by preventing apoptosis due to oxidative reactions. Objective : find out more about the effects of red dragon fruit on reducing blood glucose levels in type 2 diabetes. Methods : Use literature studies from both national and international journals by summarizing the topic of discussion and comparing the results presented in the article. Results : Type 2 diabetes mellitus is the most common form of diabetes in the world, about 90% of global cases. Traditional medicine that is commonly used is red dragon fruit. Red dragon fruit is believed to have the effect of reducing blood glucose levels because dragon fruit contains antioxidant compounds in the form of flavonoids which are protective against damage to Beta cells as a producer of insulin and can increase insulin sensitivity. Dragon fruit with a higher dose has a tendency to decrease blood glucose more to people with type 2 diabetes mellitus. Conclusion: dragon fruit has the effect of lowering blood glucose levels in people with type 2 diabetes mellitus because it contains fiber that is able to bind water in the intestine, and contains antioxidants and bioactive compounds and is able to inhibit free radical compounds.